The association between paraoxonase 1 gene polymorphisms and polycystic ovarian syndrome - Gu, H. F.; Mou, M.; Liang, Z. G.; Sun, C.; Ren, X. Y.; Xiao, Y. B. (Cellular and Molecular Biology, 2016)
Some studies investigated the association of paraoxonase 1 (PON1) polymorphisms with polycystic ovarian syndrome (PCOS) risk. However, the result was still inconsistent. The aim of this study was to investigate whether there is an association between the PON1 polymorphisms and PCOS risk. Electronic databases, such as PubMed, EMBASE, and China National Knowledge Infrastructure (CNKI) databases, were searched for identification of the studies. The associations between PON1 polymorphisms and PCOS risk was quantified using ORs with 95% CIs. A total of 8 eligible studies with 2272 cases and 1811 controls were included in this meta-analysis. PON1 Leu55Met polymorphism was associated with a significantly increased risk of PCOS (OR=1.31; 95%CI, 1.10-1.55). However, no association was found in Asians and Caucasians (Table 2). We also found that PON1 Q192R polymorphism was associated with a significantly increased risk of PCOS (OR=1.81; 95%CI, 1.17-2.82). Additionally, this polymorphism increased PCOS risk in Asians (OR=1.26; 95%CI, 1.13-1.41). Furthermore, PON1 C108T polymorphism showed increased PCOS risk (OR=1.46; 95%CI, 1.08-1.97). No association between this polymorphism and PCOS risk was found in Asians and Caucasians. In conclusion, this meta-analysis suggested that PON1 polymorphisms were associated with PCOS risk.